Evidence Using Forensic Laboratory in Revealing the Crime of Murder - Yudistira, I Wayan Arif; Widijowati , RR. Dijan (Dinasti Research, 2023)
Murder is an act committed by anyone who intentionally takes the life of another person. The process of disclosing the crime of murder can be assisted by involving forensic laboratories in it. This study aims to analyze the role of forensic laboratories and the efforts made by the National Police to involve forensic laboratories in evidence to help reveal the crime of murder based on Decision Number 111/Pid.B/2015/PN Spg. The theories used included the legal theory of evidence and the theory of law enforcement. The analysis used in this research is a qualitative descriptive analysis. The results showed that the function and role of forensic laboratories in relation to the judicial process as a means of proof in court is to corroborate/give certainty to information, determine cause-and-effect relationships, prove whether or not certain factors or phenomena are true, make laws or arguments from a phenomenon if it has been proven true, and be a means of proof in court in determining the causes of death of a person so that it will be more supportive in the criminal justice process.